Analysis of the Quality of Subdistrict Integrated Administration Services (PATEN) at the Samarinda Ilir Sub-District Office in Samarinda City - Asnar Asnar (Asian Journal of Social and Humanities, 2024)
This study was conducted with the aim of analyzing the Quality of Subdistrict Integrated Administration Service Delivery (PATEN) at the Samarinda Ilir District Office, Samarinda City, along with its supporting and inhibiting factors. Research methods with a qualitative approach, sampling as informants with purposive sampling techniques  and accidental sampling techniques. Data collection techniques, with in-depth interviews, participatory observations, and documentation studies. Data analysis techniques with Miles and Huberman's interactive model data analysis techniques. The results showed that the overall quality of patent implementation at the Samarinda Ilir District Office, Samarinda City, was good, which was proven through measuring the five dimensions of public service quality analysis, namely reliability, responsiveness, certainty, empathy, and tangibility. The supporting factors, namely very adequate office service facilities, such as the use of computer devices and printers that are adequate in number, queuing machines and special counters that ensure order in the queue during the service process, air conditioning that provides comfort, both for employees and the community served, television as a means of entertainment for the community as well as to eliminate community saturation in the service process,  as well as comfortable seating for the community during the service process, while the inhibiting factor is still not yet otpimal socialization to the community by the village and the Head of RT that several licensing services, such as Building Permits (IMB), State Land Opening Permits (IMTN), and Micro Business Permits (IUM) can be managed in the sub-district with criteria and conditions that have been determined in accordance with the provisions laws and regulations.